The Correlation Between Vocabulary Mastery and Reading Comprehension Skills Among Ninth Grade Students of SMP Negeri 1 Palasa - Fadhilatul Jannah; Abdul Gafur Marzuki; Zul Aini Rengur (Varied Knowledge Journal, 2026)
This research aims to determine and analyze the correlation between students' vocabulary mastery and their reading comprehension in grade IX of SMP Negeri 1 Palasa. Mastering vocabulary is one of the important things that affects students' ability to understand the text they read, such as understanding the main idea, detailed information, and implied meaning in the reading. The method used in this research is a quantitative approach with a correlational design. The subjects of this research involved 69 students from grade IX at SMP Negeri 1 Palasa. Data were collected by administering tests to measure vocabulary mastery and tests to measure reading comprehension. The data obtained were analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, the Pearson Product-Moment correlation test, and the Hypothesis test. The results showed that there was a positive and significant correlation between students' vocabulary mastery and reading comprehension, with a correlation value of (r = 0.597; p = 0.001). This is included in the moderate correlation category. These results indicate that students who are better at mastering vocabulary usually have higher reading comprehension abilities. This research shows that vocabulary mastery has a very important role in improving students' reading abilities. Therefore, teachers are encouraged to focus more on vocabulary development when teaching reading by using a variety of effective exercises and learning strategies. Furthermore, this research is expected to serve as a reference for future researchers examining other factors that influence students' reading comprehension.